Las disartrias - González V., Rafael A.; Bevilacqua R., Jorge A. (Revista Hospital Clínico Universidad de Chile, 2012)
The dysarthrias are a group of motor alterations of the speech as consequence of a neurological impairment that represent the 54% of the total of disorders that impair oral communication. Several types of dysarthrias could be determined according to the location of the causing lesion, the neurological mechanisms implicated in its generation, and functional characteristics of the speech. Clinical evaluation of the dysarthrias should include the clinical history, physical examination and the motor assessment of the speech. Prognosis is determined by the etiology and severity of the disorder. The objective of the treatment is to satisfy daily communicational needs of the patient in consideration to the underlying neurological condition.